Innovative α-Cryptoxanthin (α-C) Anti-Aging Serum Based on Lecithin and Hyaluronic Acid in a Self-Emulsifying Delivery (SED) System - Jess Henry Aryasatya (CV. Publikasi Indonesia, 2026)
Skin aging is not only due to complex biological processes but also affected by exposure to ultraviolet (UV) radiation. Exposure to UV radiation triggers the formation of Reactive Oxygen Species (ROS), hyperpigmentation, decreased elasticity, and collagen production. α-cryptoxanthin (α-C), one of the carotenoids with significant antioxidant, anti-inflammatory, and photoprotective properties. However, its use in serum preparations is still very limited. α-C also has lipophilic properties and low solubility in water. Therefore, this study aims to develop an anti-aging serum α-cryptoxanthin based on lecithin-hyaluronic acid using a self-emulsifying delivery (SED) system as an approach to improve delivery stability and potential effectiveness of active ingredients. The method used is a non-experimental study by collecting data, recording, and processing literature materials. Eligible studies were identified through searches on PubMed, Scopus, Google Scholar, Web of Science, Wiley, and ScienceDirect from 2016–2026. The results showed that α-C provides indirect photoprotective by neutralizing ROS due to UV exposure, reducing hyperpigmentation and supporting skin structure through stimulation of collagen production. Hyaluronic acid also improves skin hydration and elasticity which all contribute to a younger skin appearance. This innovation also supports the Sustainable Development Goals (SDGs) point 3 (Good Health and Well-Being) through the development of skin care concepts and point 12 (Responsible Consumption and Production) by encouraging the use of natural active ingredients and sustainable cosmetic formulation innovations.